Determinantes sociales del gasto catastrófico en salud en Colombia: Un análisis multinivel (2021)
Objective: The study aimed to analyze the differences in the level of the Catastrophic Health Expenditures (CHE) of Colombian households and its association with the contextual factors at the level of department. Methods: We conducted a secondary analysis of 87.201 households from the National Survey of Household Income and Expenditures 2016-1017 in Colombia and from other sources for the contextual variables of the department. The incidence and intensity of CHE were analyzed descriptively, and we used a multilevel logistic regression to explain the CHE within and between departments for the Colombian households. Results: 1.76% of Colombian households faced CHE. The incidence increased in households whose household head had a permanent disability, was 60 years or older, did not have any level of education, and was not insured under the healthcare system. 50% of the out-of-pocket health expenditures of households that faced CHE were shared in drugs and medical consultations. 1.32% and 3.36% of households located in urban and rural areas had CHE, respectively. It was found important differences in the levels of CHE between departments related to the number of healthcare professionals, hospital beds, and multidimensional poverty as contextual factors. The incidence of CHE was higher in the departments of Boyacá, Cauca, Choco, and Nariño. The multilevel model shows that between 4.85% and 5.64% of the variability in the explanation of the CHE is due to the department. Conclusions: We observed a modest explanation of CHE attributable to the department of residence. This variability is due to the broad clusters found for Colombia departments; however, it is an important percentage to consider in the public policy agenda. Financial protection against CHE is an important issue at the micro and macro level, improve the access and availability to healthcare professionals and medicines may reduce the incidence of CHE of vulnerable groups for the departments of Colombia.